MINORITY LANGUAGES UNDER NAZI OCCUPATION - Hamans, Camiel (Scripta Neophilologica Posnaniensia, 2019)
This paper discusses the special interest the Third Reich ideologues had for Germanic minority languages. In particular, the situation in Friesland, Flanders and Brittany is addressed. Moreover, it is made clear how German linguists from that period tried to annex Wallonia as an original Germanic area. Finally, the consequences of this cooperation with the Nazi occupier for the post-war discussions about these minority languages are briefly indicated.